Sacrococcygeal extraspinal ependymoma: A case report - Akpolat, Nusret; Bozlak, Nurten; Kazez, Ahmet; Köseo?ullari, Aysel (My University, 2003)
Ependymomas, the common glial tumors of the spinal cord, occur occasionally outside the central nervous system and are called extraspinal ependymomas (ESE). ESE, which are clinically confused with other sacrococcygeal tumors, are rarely seen and found primarily in the sacrococcygeal region during childhood. We report a case of a seven-year-old boy presenting with a midline mass (6 cm diameter) over his coccyx. The solid mass was diagnosed as maxillopapillary type of ependymoma. Clinical and histopathological features of the case are described and literature reviewed.
Keywords: Extraspinal ependymoma; Subcutaneous sacrococcygeal tumor